Estimation of Global Structural and Transport Properties of Peptides through the Modeling of their CZE Mobility Data - Piaggio, María Virginia (2010)
Peptide electrophoretic mobility data are interpreted through a physicochemical CZE model, providing estimates of the equivalent hydrodynamic radius, hydration, effective and total charge numbers, actual ionizing pK, pH-near molecule and electrical permittivity of peptide domain, among other basic properties. In this study, they are used to estimate some peptide global structural properties proposed, providing thus a distinction among different peptides. Therefore, the solvent drag on the peptide is obtained through a characteristic friction power coefficient of the number of amino acid residues, defined from the global chain conformation in solution. As modeling of the effective electro-phoretic mobility of peptides is carried out in terms of particle hydrodynamic size and shape coupled to hydration and effective charge, a packing dimension related to chain conformation within the peptide domain may be defined. In addition, the effective and total charge number fractions of peptides provide some clues on the interpretation of chain conformations within the framework of scaling laws. Furthermore, the model estimates transport properties, such as sedimentation, friction and diffusion coefficients. As the relative numbers of ionizing, polar and non-polar amino acid residues vary in peptides, their global structural properties defined here change appreciably. Needs for further research are also discussed.